2006
DOI: 10.1007/s00420-006-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of talc-related respiratory morbidity among employees of a rubber industry in Shiraz-Iran

Abstract: These results that are in full agreement with our preliminary observations, support the notion that occupational inhalation exposure to talc is associated with both acute and chronic respiratory disorders and induces bronchitis and interstitial lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
6
16
1
Order By: Relevance
“…The researchers noted a statistically significant increased prevalence of respiratory complaints (i.e., cough, sputum, wheezing, and dyspnea) among production unit workers compared to executive employees. These results are similar to those of Neghab et al (2007), Ghasemkhani et al (2006), Jaén, Zock, Kogevinas, Ferrer, and Marín (2006), and Jaakkola et al (2011). In contrast, in the study by Meijer, Heederik, and Kromhout (1998), rubber workers with chronic respiratory symptoms were not found to have higher rates than the control group.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The researchers noted a statistically significant increased prevalence of respiratory complaints (i.e., cough, sputum, wheezing, and dyspnea) among production unit workers compared to executive employees. These results are similar to those of Neghab et al (2007), Ghasemkhani et al (2006), Jaén, Zock, Kogevinas, Ferrer, and Marín (2006), and Jaakkola et al (2011). In contrast, in the study by Meijer, Heederik, and Kromhout (1998), rubber workers with chronic respiratory symptoms were not found to have higher rates than the control group.…”
Section: Discussionsupporting
confidence: 85%
“…[ Workplace Health Saf 2013;61(5):213-220. ] by Neghab et al (2007), workers exposed to talc had a significantly higher prevalence of pulmonary symptoms than controls. Also, pulmonary function tests showed that workers exposed to talc had significant decreases in their mean percentage predicted vital capacity (VC; i.e., the maximum amount of air an individual can expel from the lungs after a maximum inhalation), forced vital capacity (FVC; i.e., the volume of air that can forcibly be expelled after full inspiration), and forced expiratory volume in 1 second (FEV 1 ; i.e., the volume of air that can forcibly be expelled in 1 second, after full inspiration).…”
Section: Research Abstractmentioning
confidence: 86%
“…Table summarizes 32 articles describing 30 cross‐sectional studies evaluating the presence of respiratory symptoms and NMRD among workers exposed to rubber manufacturing emisssions . Occupational cohorts ( n = 10 896 workers in total) across studies varied from 34 to 1820 workers, and included facilities from the United States ( n = 14), Sweden (6), India (3), Iran (3), Italy (1), Netherlands (1), Poland (1), and Turkey (1).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the use of technological coadjuvants producing a chemical or biochemical action is forbidden by European regulations on virgin olive oil production (Regulation EEC 1513/2001), so currently talc is the only coadjuvant allowed due to its exclusively physical action (Cert et al, 1996). In contrast, literature reports on epidemiological cancer studies have identified talc as a risk factor (Wild, 2006;Neghab et al, 2007;Ramanakumar et al, 2008). The use of common salt (NaCl) as a physical-acting coadjuvant has been reported recently with similar or slightly lower extraction yields to those obtained with talc (Cruz et al, 2007).…”
Section: Introductionmentioning
confidence: 85%